2005
DOI: 10.1309/c4bk-7gqv-8e5x-u2tl
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget FISH and LOH Analyses at Chromosome 3p in Non-Small Cell Lung Cancer and Adjacent Bronchial Epithelium

Abstract: Multitarget fluorescence in situ hybridization (FISH; LAVysion, Vysis, Downers Grove, IL) targeting chromosomes 6p11-q11, 7p12, 8q24, and 5p15.2 was compared with results of microsatellite studies at chromosome 3p to identify molecular changes associated with tobacco use and tumor development in non-small cell lung cancer (NSCLC). Analyses were performed on 26 NSCLCs and matched benign bronchial epithelium; samples from 10 patients without NSCLC served as control samples. Significant molecular differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…This finding was validated by correlation with FISH results. Although chromosome loss can be difficult to identify with FISH on paraffin sections as a result of nuclear truncation and overlapping nuclei, a good, but not perfect, correlation has been observed in prior studies [35,36]. Given the loss of 17p13 in the recurrent but not in the primary CSs of the present and previous prior studies [28][29][30]33,34], it is possible that p53 mutations may represent a late event in the progression of CSs.…”
Section: Discussionsupporting
confidence: 53%
“…This finding was validated by correlation with FISH results. Although chromosome loss can be difficult to identify with FISH on paraffin sections as a result of nuclear truncation and overlapping nuclei, a good, but not perfect, correlation has been observed in prior studies [35,36]. Given the loss of 17p13 in the recurrent but not in the primary CSs of the present and previous prior studies [28][29][30]33,34], it is possible that p53 mutations may represent a late event in the progression of CSs.…”
Section: Discussionsupporting
confidence: 53%
“…However, some studies have raised the question that whether normal adjacent tissues can truly represent normal tissues in these type of studies due to a ''field'' effect (35,36). They suggested that, in some cases, tissues adjacent to cancer, although appearing morphologically normal, may contain genetic changes associated with cancer (35,36), which might even influence gene expression (35). Therefore, difference in baseline or normal tissue collection might also contribute to controversial reports on telomere-associated protein expression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LOH is common to all human solid tumors and allows expressivity of recessive loss of function mutations of tumor suppressor genes. Therefore, detection of recurrent LOH in a chromosome region is now considered critical evidence of localization of tumor suppressor genes [3,[25][26][27][28] . In the previous study, initial LOH scanning was carried out in 83 sporadic colorectal carcinoma samples with 21 highly polymorphic markers on chromosome 1.…”
Section: Discussionmentioning
confidence: 99%